VD_FINDINFO HC / 2013 / 688 vom 12. November 2013 - VD Tribunal cantonal (2013)
DOMICILE EN SUISSE, LIEU DE L'EXÉCUTION, COMPÉTENCE DIRECTE, COMPÉTENCE INTERNATIONALE | 2 al. 1 CL, 5 ch. 1 CL, 112 LDIP, 113 LDIP